2020
DOI: 10.3389/fneur.2020.00756
|View full text |Cite
|
Sign up to set email alerts
|

Gonadal Steroids and Sperm Quality in a Cohort of Relapsing Remitting Multiple Sclerosis: A Case-Control Study

Abstract: Introduction: Evaluation of the hypothalamic-pituitary-testicular axis and sperm analyses are not a standard examination of patients with Relapsing-Remitting Multiple Sclerosis (RRMS). Methods: This is a prospective-case-controlled study. Patients, aged 18-55, with a confirmed diagnosis of RRMS, naïve to any DMT were enrolled. Controls were men with normal evaluation who acceded to the Andrology Center of Catania in a contemporary matched randomized fashion to the group of RRMS patients. The aim of the study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
2
6
0
Order By: Relevance
“…Data regarding the prevalence of hypogonadism in men with MS has been mixed. While one study showed an increased prevalence of hypogonadism in MS (Bove et al, 2014), other studies showed men had levels of hypogonadism comparable to the general population (Tomassini et al, 2005;D'Amico et al, 2020D'Amico et al, , 2021, two of which additionally reported no impact of MS on male fertility (D'Amico et al, 2020(D'Amico et al, , 2021. This study provides supportive evidence that men with MS have a high prevalence of hypogonadism, although not as high as the 40% previously reported.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Data regarding the prevalence of hypogonadism in men with MS has been mixed. While one study showed an increased prevalence of hypogonadism in MS (Bove et al, 2014), other studies showed men had levels of hypogonadism comparable to the general population (Tomassini et al, 2005;D'Amico et al, 2020D'Amico et al, , 2021, two of which additionally reported no impact of MS on male fertility (D'Amico et al, 2020(D'Amico et al, , 2021. This study provides supportive evidence that men with MS have a high prevalence of hypogonadism, although not as high as the 40% previously reported.…”
Section: Discussionsupporting
confidence: 65%
“…Prevalence of hypogonadism in men with multiple sclerosis (MS) has been reported to be as high as 40% and low testosterone levels have been correlated with increased level of disability in a single center cohort from which archival serum samples were tested (Bove et al, 2014). However, the reported incidence of hypogonadism in men with MS and its association with disability has not yet been replicated in other studies (Tomassini et al, 2005;D'Amico et al, 2020;D'Amico et al, 2021). This study sought to assess prevalence of hypogonadism in a population of men with MS using an approach that could be easily replicated in a neurology clinic: we used a standard endocrinological screening instrument and systematically assessed male patients who were seen at an MS center.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the authors reported a correlation between low testosterone levels and disability (54). Other studies however, were not able replicate these findings (53).…”
Section: Clinical Findingsmentioning
confidence: 93%
“…Several studies have found lower testosterone levels in men with MS, compared to healthy age-matched subjects (51)(52)(53). In a cohort of 96 men with relapsing remitting MS, mean age of 40 years and disease duration <10 years, 39% of patients were hypogonadal with no compensatory rise in luteinizing hormone, suggesting central hypogonadism (54).…”
Section: Clinical Findingsmentioning
confidence: 98%
“… 38 , 94 , 95 Low testosterone has been correlated with increased disability scores, 38 , 96 and recent studies have trialled the use of testosterone as a therapeutic for MS with varied outcomes. 38 Given that testosterone can cross the blood–brain barrier and acts directly on neurons, 97 it is possible that testosterone may be neuroprotective in MS. 38 , 94 , 96 However, more research is required to validate these findings and rule out confounders, since hypogonadism can be induced by chronic disease states. 38 …”
Section: Translation Of Immunological Impact Of Sex Hormonesmentioning
confidence: 99%